Political science research methods - Johnson, Janet Buttolph 1950-; Reynolds, H. T. (Henry T.); Mycoff,Jason D. (SAGE Reference/CQ Press, 2016)
Step by step, Political Science Research Methods walks students through the logic of research design, carefully explaining how researchers choose which method to employ. The Eighth Edition of this trusted resource offers a greater emphasis on the ways in which particular methods are used by undergraduates, expanded coverage of the role of the Internet in research and analysis, and more international examples. New to this edition: Streamlined content that delivers greater clarity of concepts and a tighter focus on what matters most; Learning objectives encourage close, focused reading and measurable takeaways; New and updated examples of research serve as touchstones throughout the book and demonstrate a greater variety of data collection methods: Greater emphasis on how particular research methods are used by undergraduate students; Expanded coverage of the role of the Internet in research and analysis; A brand new annotated research article in Chapter 15.